Application of PEG-CdSe@ZnS quantum dots for ROS imaging and evaluation of deoxynivalenol-mediated oxidative stress in living cells. (December 2020) - Zhou, You; Lv, Yan; He, Chuxian; Lin, Xianfeng; Li, Cong; Xu, Wei; Duan, Nuo; Wu, Shijia; Wang, Zhouping
Abstract: Deoxynivalenol (DON), a trichothecene mycotoxin, has attracted global attention due to its prevalence and substantial effects on animal and human health. DON induces the upregulation of intracellular reactive oxygen species (ROS) by disrupting the normal mitochondrial functionality, which causes oxidative stress, cell apoptosis, and even severe disorders. The aim of present work is to develop a simple, convenient, and in situ method for monitoring ROS and evaluating DON-mediated oxidative stress. Herein, polyethylene glycol-modified CdSe@ZnS quantum dots (QDs) were employed as simple and convenient nanoprobe for ROS imaging and oxidative stress evaluating induced by DON in living cells. The results demonstrated 5 ppm QDs nanoprobe can be easily loaded into cells via endocytosis without readily observable oxidative effects. Once in presence of DON, the augmented ROS directly oxidize the QDs nanoprobe, which leads to the destruction of the QDs structure and quenched fluorescence. According to the weakened fluorescence intensity (FI), the oxidative damage mediated by DON can be rapidly monitored and found that the oxidative stress was the most severe when the DON concentration exceeded 10 ppm. The developed QDs nanoprobe is also suitable for assessing other mycotoxins and chemicals. We hope it will be beneficial for the early screening of toxic and harmful substances in in vitro toxicology. Graphical abstract: Image 1 Highlights: A simple, convenient and in situ method for monitoring ROS and evaluating DON-mediated oxidative stress was developed. The QDs nanoprobe was successfully applied for imaging ROS in living cells. ROS production tended to be saturated and the oxidative stress was the most severe when DON concentration exceeded 10 ppm. The developed nanoprobe is also beneficial for early screening for other toxic and harmful substances.